Lemmus amurensis Vinogradov 1924 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
30. Amur Brown Lemming Lemmus amurensis French: Lemming de 'Amour / German: AmurLemming / Spanish: Lemming del Amur Other common names: Amur Lemming Taxonomy. Lemmus amurensis Vinogradov, 1924, Pikan, on Zeya River, a tributary of Amur River, Siberia, Russia. Taxonomy and distribution of L. amurensis are not definitely known, and some consider it part of L. sibiricus. Others synonymize flavescens with sibiricus. Two subspecies recognized. Subspecies and Distribution. L.a.amurensisVinogradov,1924—fromETransbaikaliaandAmurRiverEalongthe SeaofOkhotskandacrossSchsofVerkhoyanskandCherskiyrangestoKolymaUpland(Russia). L. a. flavescens Vinogradov, 1925 — Kamchatka (Russia). Descriptive notes. Head-body 86-119 mm, tail 9-6-14-7 mm; weight 16-2-51 g. The Amur Brown Lemming is similar to the Siberian Brown Lemming (L. sibiricus) but is considerably smaller and has brighter pelage. Dorsum is brown, cheeks are rusty or yellow-buff, snoutis rusty, and gray venter is usually washed rusty or buffy. Dark medial stripe runs ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 292-293, DOI: 10.5281/zenodo.6707142 ...